Hubungan Power Otot Tungkai Dengan Kemampuan Shooting Sepakbola Pemain Uir Soccer School Pekanbaru Indonesia - Rices Jatra; Sarwaki Sarwaki (Indonesian Journal of Physical Education and Sport Science)
The purpose of this study was to determine the relationship between leg muscle power and soccer shooting ability of UIR Soccer School Pekanbaru players. This type of research is correlational research. The population in this study were SSB UIR Soccer School (USS) players, totaling 58 people. The sampling technique was cluster sampling of players aged 14-15 years, totaling 20 people. The instrument used is a standing broad jump test and a shooting test for soccer games. The results of calculations carried out obtained a correlation index of 0.472. This value is in the range between 0.4 - 0.70 with a Medium correlation category. The rtable value in the sample of 20 or DF = 18 people is 0.444. Thus, the value of r arithmetic > r table or 0.472 > 0.444. The value of t count = 2.27 and the value of t table is 2.10. Thus, t count > t table or 2.27 > 2.10. The conclusion of this study is that there is a significant relationship between leg muscle explosive power and soccer shooting ability of SSB UIR Soccer School Pekanbaru players. The calculated r value = 0.472 and the table r value = 0.444. The calculated t value = 2.27 and the t table value = 2.10.